Impact of microbial proteases on biotechnological industries. Issue 2 (3rd July 2017) - Banerjee, Goutam; Ray, Arun Kumar
Abstract: The demand of enzymes in industrial sectors is increasing rapidly due to their economical and ecological advantages. Micro-organisms produce different types of extracellular enzymes for maintaining their own metabolism, defense, and normal physiological condition. Among several enzymes, proteases have gained special attention in industrial sectors. Several sources of extracellular enzymes are reported by various researchers, but enzymes obtain from microbial sources have high demand in industries due to lower cost, high production rate, availability, stability, and diversity. Among micro-organism, bacteria and fungi are reported to be good sources of different types of proteases such as alkaline protease, cysteine protease, aspartate protease, and metallo protease. In this review, we have summarized the available information about the sources of bacterial and fungal proteases, their purification strategies and their temperature and pH optima. Due to huge competition, companies are trying to reduce their manufacturing cost and that's why microbial sources of enzymes are important. However, genetically engineered strains or engineered proteases have much more importance over natural isolates/protease in industries due to higher production rate and other advantages. Here we have also summarized the important applications of protease in different industries such as, paper mill, starch degrading sector, food processing factories, and detergent making companies.